A green pharmacy: quantifying medicinal plant use in the Sohagi Barwa Wildlife Sanctuary - Ojha, Anju; Bala, Chandra; Pandey, Santosh (Ethnobotany Research and Applications, 2025)
Background: Indigenous communities have a rich tradition of using plants for medicinal purposes, with this knowledge passed down through generations. However, habitat loss, unsustainable harvesting, and declining traditional knowledge threaten this valuable resource. Documentation of traditional practices practiced by the Indigenous communities helps to link modern medicine with traditional knowledge. Methods: Eighty-six participants in the Sohagi Barwa Wildlife Sanctuary were interviewed. The collected data were analyzed to assess several indices, namely based on the Consensus Factor, Usage Value, Fidelity Level, Relative Frequency of Citation, and the Used Report. Indices based on these parameters’ measures ethnomedicinal knowledge’s importance, value, and comprehensiveness for all the documented plant species. Results: The study identified 95 medicinal plant species across 39 families, with the Fabaceae family being the most represented. Almost one-third of the medicinal formulations were found to be derived from decoction methodology. Decoction was the most common method of preparation, accounting for 33% of formulations. Digestive diseases had the highest Informant Consensus Factor (ICF) of 0.95. Among the plants, Senegalia catechu (L.f.) P.J.H.Hurter & Mabb. stood out, having the highest Use Value (UV) of 1.28 and the highest Relative Frequency of Citation (RFC) at 0.98. Moreover, it also achieved a perfect Fidelity Level (FL) of 100% for treating mouth ulcers. These findings indicate that traditional medicinal plant use remains prevalent in research and largely unexplored. Conclusions: Identifying and documenting medicinal plants is crucial in safeguarding cultural heritage, fostering scientific discovery, and promoting sustainable healthcare practices for future generations. Working together, indigenous communities, scientists, and conservationists can unveil the wealth of natural remedies. Keywords: Ethnomedicine, Medicinal Plants, Traditional Knowledge, Biodiversity Conservation, Sustainable Healthcare, Sohagi Barwa, Sanctuary